Enzymatic and mechanical lipolysis in the submentonian and submandibular regions. A integrative literature review (Research, Society and Development, 2025)
Increased volume in the submental region may be associated with various factors, such as genetic conditions, positioning of the maxillary and mandibular bones and accumulation of fat in the region. The accumulation of adipose tissue in this area generates excess skin and adipose tissue under the mandible, causing the appearance of a double chin. This aspect can lead patients to seek procedures to improve their neck aesthetics. Solutions to this problem could be jowl reduction through enzymatic or mechanical lipolysis, through an aesthetic procedure for the mechanical removal of submental adipose tissue. Objective. This study reviewed the narrative literature on the use of enzymatic jowl lipolysis and mechanical removal. Methodology. A survey was carried out of articles published between 2006 and 2024, in Portuguese and English, which addressed the two techniques. Results. One hundred and four studies were found in the databases. After exclusion due to duplication, analysis of titles, abstracts and incomplete texts, only 7 articles met the eligibility criteria. Liposuction of the jowls, subdivided into mechanical and enzymatic techniques, was described with similar frequency, depending on the indication and technical protocol. Conclusion. Both techniques are good for controlling the reduction of submentual fat with the aim of obtaining a more harmonious contour of the region, and are effective within Orofacial Harmonization, when well indicated and well performed.